Mucocele of the vermiform appendix: diagnostic challenges and therapeutic approach - Cunha,Carlos Magno Queiroz da (2019)
ABSTRACT Introduction: Mucocele of the appendix is defined as the obstructive dilatation of the vermiform appendix by the abnormal accumulation of mucinous substance in its lumen. Imaging tests may be useful, but they commonly fail to evidence the etiology in question. Regarding the therapeutic approach, there are different options for treatment. Appendectomy was routinely used in simple cystadenomas, with good results. However, in cases of neoplasias, more aggressive resection is necessary, and the therapeutic course of choice is the right hemicolectomy. Case report: Patient presented to the surgery outpatient clinic with magnetic resonance imaging presenting an adnexal cyst of about 11.0 × 4.5 cm on the right. The patient had pain in the right iliac fossa for 6 months. Due to the radiological finding and persistence of the clinical picture, videolaparoscopy was performed, and an appendicular mass suggestive of mucocele was identified. A laparoscopic appendectomy was performed, with no signs of mucus extravasation. Histopathological analysis confirmed the diagnosis. Discussion: Mucocele is rarely diagnosed effectively in the preoperatively. In this context, imaging tests do rarely evidence such etiology. Given the importance of preoperative diagnosis for the definition of conduct, it is essential that this condition be always taken into account as a diagnostic hypothesis.